The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7752/jpes.2016.03139
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The purpose of this study was to investigate the effect of IAAF Kids' Athletics on motivation, physical fitness and track and field event performance of children (11-12 years old). The IAAF Kids' Athletics is a track and field teaching program that was developed by the IAAF (International Association of Athletics Federation). In total 215 elementary students participated in the study. IAAF Kids' Athletics was implemented in an experimental group and the traditional skill teaching method for track and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…The findings of our study are in line with the previous study conducted by Petros et al (2016). The study (Petros et al, 2016) was conducted on elementary school students aged 11 to 12 years for 12 weeks and reported significant improvement in all motor fitness components in Kid's Athletics group than the traditional method group. Petros et al (2016) also suggested that Kid's Athletics may motivate the elementary students to learn track and field as a new sport.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of our study are in line with the previous study conducted by Petros et al (2016). The study (Petros et al, 2016) was conducted on elementary school students aged 11 to 12 years for 12 weeks and reported significant improvement in all motor fitness components in Kid's Athletics group than the traditional method group. Petros et al (2016) also suggested that Kid's Athletics may motivate the elementary students to learn track and field as a new sport.…”
Section: Discussionsupporting
confidence: 91%
“…The study (Petros et al, 2016) was conducted on elementary school students aged 11 to 12 years for 12 weeks and reported significant improvement in all motor fitness components in Kid's Athletics group than the traditional method group. Petros et al (2016) also suggested that Kid's Athletics may motivate the elementary students to learn track and field as a new sport. In addition, the Kid's Athletics programme also helped the students to ISSN 1993-7989 (print).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bila dilihat dari karakteristik gerakannya menurut (Rumini, 2014), kids athletics memiliki gerak dasar yang terdiri dari unsur lari, lompat dan lempar. Mengacu pada konsep tersebut, maka pengembangan kemampuan kids athletics anak harus melalui pendekatan latihan fisik yang memiliki karakteristik berupa gerak dasar motorik lari, lompat dan lempar (Petros et al, 2017). (Rumini, 2014).…”
unclassified